35 Years of Child Rights and the Emerging Right to a Healthy Environment - Mensah, Cocou Marius; Brajović Mensah, Zorica (Children’s Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges: Exploring Opportunities and Challenges, 2025)
As of November 20, 2024, 35 years have passed since the adoption of the United Nations Convention on the Rights of the Child (UNCRC) in 1989, a unique and binding instrument that enshrined, for the first time in international law, a comprehensive set of rights for children across the globe. While the UNCRC has driven significant progress since its adoption in 1989, emerging challenges, particularly digitalisation and the climate crisis, reveal critical gaps in its implementation. This article evaluates three decades of achievements in child rights protection, identifies persistent shortcomings, and examines the urgent need to address environmental degradation as a violation of children’s rights. Through an analysis of international legal provisions and landmark cases, the authors argue for stronger enforcement mechanisms to uphold children’s right to a healthy environment.